Reproductive profile of Aedes aegypti and Aedes albopictus from an urban area endemic for arboviruses in the Northeast region of Brazil (Research, Society and Development, 2021)
Aedes aegypti and Aedes albopictus are mosquitoes with a great impact on public health as they are vectors of important arboviruses. The objective was to investigate the reproductive profile of these two vectors in homes and vacant lots in the rainy and dry seasons. In 2017, four inspections were carried out in 100 properties in five districts of Caxias, Maranhão (400 inspections), with repetitions in 2018, totaling 800 inspections. A total of 3,837 immature forms were collected in 11.6% (N = 93) of the inspections, being 3,394 Ae. aegypti (88.4%) and 443 Ae. albopictus (11.6%). The largest number of breeding sites were in the water storage group with 78 containers (70.9%) and 2,768 immature (72.1%), with 2,663 Ae. aegypti (96.2%) and 105 Ae. albopictus (3.8%) found only in households. In vacant lots, a greater number of Ae. albopictus (N = 228; 67.7%), in relation to Ae. aegypti (N = 109; 32.3%), with flasks being the most frequent containers (N = 12.1%), contributing 48.9% (N = 165) of the immature forms collected in the land. The highest larval density was found during the rainy season of the two years (N = 3,076; 80.1%), and in 2017, there was a moderate and positive correlation between rainfall and the number of immatures of Ae. aegypti (rs = 0.46; p = 0.05). It was evident that water storage containers are still the vectors' preference, and that the proximity to vacant lots does not exert much influence on the reproduction of these mosquitoes that prefer homes.